2000
DOI: 10.1111/j.1349-7006.2000.tb00882.x
|View full text |Cite
|
Sign up to set email alerts
|

Production of a Single‐chain Variable Fragment Antibody Recognizing Type III Mutant Epidermal Growth Factor Receptor

Abstract: The type III deletion mutant of the epidermal growth factor receptor (EGFR) is a potential target in diagnostic and therapeutic approaches for those glioblastomas characterized by its expression. We previously raised a mouse monoclonal antibody, 3C10 (IgG2b) specifically recognizing this mutant EGFR. In this study, a single-chain variable fragment (scFv) antibody was produced. Partial determination of its N-terminal amino acid sequence and preparation of adequate primers for variable heavy chain (V H ) and var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 16 publications
(24 reference statements)
0
15
0
Order By: Relevance
“…16,17 Our group generated the mouse monoclonal antibody 3C10 and a recombinant single-chain variable fragment (scFv) antibody that specifically recognizes the de novo glycine residue of EGFRvIII. 18,19 Further, we constructed human T cells that expressed chimeric antigen receptor (CAR) targeting the EGFRvIII antigen (3C10-CAR). 20,21 CARs are genetically constructed from scFvs connected by a transmembrane hinge region, the T-cell signaling complex, and costimulatory signaling domains (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…16,17 Our group generated the mouse monoclonal antibody 3C10 and a recombinant single-chain variable fragment (scFv) antibody that specifically recognizes the de novo glycine residue of EGFRvIII. 18,19 Further, we constructed human T cells that expressed chimeric antigen receptor (CAR) targeting the EGFRvIII antigen (3C10-CAR). 20,21 CARs are genetically constructed from scFvs connected by a transmembrane hinge region, the T-cell signaling complex, and costimulatory signaling domains (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Based on a review of scientific literature and publicly available databases, the amino acid sequences for seven monoclonal antibodies (mAbs) (four murine and three human) specific for EGFRvIII were obtained and used to synthesize single-chain variable fragment (scFv) genes (Wikstrand et al, 1995;Lorimer et al, 1996;Reist et al, 1997;Nakayashiki et al, 2000;Weber, 2005). The amino acid sequences for variable light and heavy chains (VL and VH, respectively) of the antibodies were combined in the following order: amino acid leader sequence (from the human GM-CSFR protein), VL, a peptide linker peptide sequence (GSTSGSGKPGSGEGS), and VH, which were reverse-translated and produced as a codon-optimized synthetic DNA (Invitrogen).…”
Section: Retroviral Vector Containing the Anti-egfrviii Car Genementioning
confidence: 99%
“…Recently, phage display cloning has become a general strategy for preparing recombinant antibodies originating from humans, [16][17][18][19][20][21][22][23] mice, 24,25) and other species. 29,30) Antibody genes are expressed as the Fab or single chain Fv (scFv) form using suitable vectors and cloning systems.…”
Section: Discussionmentioning
confidence: 99%
“…bone marrow cells, lymph node cells, peripheral blood lymphocytes, spleen cells, and hybridoma cells. It has been reported that recombinant human mAb fragments against viral pathogens [16][17][18][19] and autoantigens, [20][21][22][23] and recombinant murine mAb fragments against various tumor-associated antigens 24,25) were successfully isolated by means of the phage display system. In this study, among the anti-CD98 h.c. mAbs, we selected HBJ127 5,7,8) as a starting material because it showed not only antigen binding activity, but also characteristic bioactivity including an inhibitory effect on cell growth 7,9,10) and lymphocyte proliferation.…”
mentioning
confidence: 99%